MASTERING BY USING PICTURE AT CULINARY PROGRAM OF STP SAHID SURAKARTA - Dian Muhammad Rifai; Sukma Shinta Yunianti (JURNAL ILMIAH EDUNOMIKA, 2021)
This research has aim to tell the reader about describing the way of using pictures in the teaching of English language in Culinary major of study in STP Sahid Surakarta. Based on the lesson plan, The class activities consisted of four steps. They are: First activity is called apperception; it is the step to make students like to learn the material and it is as the step to introduce the materials about culinary. Second is delivering materials by using pictures as visual media. The activity iof this step including learning four skills; listening, writing, speaking and reading. Third step is practicing the skill that has benn learned. It is used to dig the students’ progress after the activities. Fourth is the assessment; it is used to asses the understanding of the students about the material and the way of the writer in the teaching of english the students by using picture. The writer get the very significant effects after using pictures when the writer teaches. These effect are gotten by the writers are: teaching using pictures can increase the interest of the students about english language, teaching using picture can make the students pay attention to the material more than before, teaching using picture can help students to memorize the english vocabulary, Teaching using of pictures can create a happy situation for the students in teaching and learning activity. The last, The pictures can enrich the technique of English teaching in Culinary Study program at STP Sahid of Surakarta.